Anti-CS1 × Anti-CD3 Bispecific Antibody (BiAb)-Armed Anti-CD3 Activated T Cells (CS1-BATs) Kill CS1+ Myeloma Cells and Release Type-1 Cytokines - Lum, Lawrence G.; Thakur, Archana; Elhakiem, Abdalla; Alameer, Lena; Dinning, Emily; Huang, Manley (Frontiers in Oncology, 2020)
Background: Multiple myeloma (MM) remains incurable despite significant advances in chemotherapy, targeted therapies, and immunotherapy. Bispecific antibody (BiAb)-armed activated T cells (BATs) have been developed for targeting and treatment of solid and hematologic malignancies. BATs are serial killers of tumor cells, secrete Th1 cytokines, and induce adaptive cellular and humoral immune responses in patients (pts). This study provides preclinical data using bispecific anti-CS1 (elotuzumab) x anti-CD3 (OKT3) antibody (CS1Bi)-armed activated T cells (CS1- BATs) that provide a strong rationale for applying CS1-BATs to pts with MM. Methods: CS1-BATs and unarmed activated T cells (ATC) were incubated with MM cell targets at various effector to target ratios (E:T) in a quantitative flow cytometry-based assay to determine the degree of cell loss relative to target cells incubated without ATC. ATC from up to 8 normal donors were armed with various concentrations of CS1 BiAb and tested against 5 myeloma cells lines for CS1-BATs-mediated killing and release of Th1 cytokines, chemokines and granzyme B. Results: CS1-BATs from normal donors killed each of 5 MM cell lines proportional to E:T ratios ranging between 1:1 to 10:1 and arming concentrations of 12.5 to 50 ng/million ATC, which was accompanied by release of Th1 cytokines, chemokines and granzyme B. CS1-BATs prepared from MM pts’ peripheral blood mononuclear cells (PBMC) showed increasing cytotoxicity and T cell expansion over time against ARH77 MM cells. The optimal arming dose of CS1Bi is 50 ng/106 ATC. Conclusions: These data demonstrate the therapeutic potential of CS1-BATs-mediated cytotoxicity and Th1 cytokines release at low E:T and support advancing their clinical development in pts with MM.